2005
DOI: 10.1002/qua.20533
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hammett sigma constants of substituted benzenes through accurate density‐functional calculation of core‐electron binding energy shifts

Abstract: ABSTRACT:For substituted benzenes such as (p-F-C 6 H 4 -Z), Linderberg et al. [1] demonstrated the validity of an equation similar to: ⌬CEBE Ϸ , where ⌬CEBE is the difference in core-electron binding energies (CEBEs) of the fluorinated carbon in p-F-C 6 H 4 -Z and that in FC 6 H 5 , the parameter is a function of the type of reaction, and is the Hammett substituent () constant. In this work, CEBEs of ring carbon atoms for a series of para disubstituted molecules p-F-C 6 H 4 -Z were first calculated using De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 9 publications
1
58
0
Order By: Relevance
“…The substituent constants were frequently correlated with the properties of atoms and bonds in the nearest vicinity of the reaction center [34-39, 41, 42, 47, 53-60], e.g., the hydrogen atom when dissociation of the COOH group was considered [37, 58,63]. The Hammett constants were also correlated with properties characterizing whole molecules [16,43,[46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substituent constants were frequently correlated with the properties of atoms and bonds in the nearest vicinity of the reaction center [34-39, 41, 42, 47, 53-60], e.g., the hydrogen atom when dissociation of the COOH group was considered [37, 58,63]. The Hammett constants were also correlated with properties characterizing whole molecules [16,43,[46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…-electron densities at p-and m-positions in monosubstituted benzenes [34] -electrostatic potential values at the ring carbon atoms [28,35,36] -electrostatic potential values at atoms of a reaction center [28,37] -topography of electrostatic potential near the molecular surface [38][39][40][41][42] -hyperpolarizability [43] -a complexed metal chemical shift [44,45] -energy of the highest occupied orbital (E HOMO ) [46,47] -energy of the lowest unoccupied orbital (E LUMO ) [16] -ionization potential [48] -electrophilicity, being a measure of stabilization in energy when the system acquires an additional electronic charge DN from the environment [28,49,50] -core electron binding energy shifts [51,52] -intramolecular charge transfer between oxygen or sulfur lone pair and an adjacent orbital, both within the reaction active center [53,54] -the so-called quantum chemical topology descriptors constructed using properties of the bond critical points, BCP, where BCP is the saddle points in the electron density [55][56][57][58] -charge of the reaction active site [42,47,59,60] -energy of p-conjugation [61] -charge of the substituent active space [58,[62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…It can be certainly concluded that a few chemical properties (electronegativity, bond multiplicity, atom size) of CA determine C1s CEBEs. In fact, it has been shown recently [47][48][49] that CEBEs calculated at DFT level are correlated with Hammett σ constants. Besides, modern ab initio calculations of CEBEs or ESCA chemical shifts [47][48][49][50][51] are far more accurate (reaching deviations 0.2 eV) than semi-empirical methods [51][52][53] that were popular a decade or two ago [54][55][56][57][58][59].…”
Section: Comparison Of Pls and Dft Resultsmentioning
confidence: 99%
“…Linear free energy relationships (LFER) were applied to the 1 H-NMR spectral data of compounds 7-13 and IR spectral. A variety of substituents were employed for phenyl substitution and fairly good correlations were obtained using the simple Hammett and the Hammett-Taft dual substituent parameter equations [25,26]. The correlation results of the substituent induced 1 H-NMR chemical shifts (SCS) of the CH3 at C5 isoxazole spins indicated different sensitivity with respect to electronic substituent effects.…”
Section: Spectroscopic Examinationmentioning
confidence: 99%